Relative intake, nutrients utilization, nutrient balance and fermantation pattern in sheep fed stay-green go brown Sorgum silage - SINGH, SULTAN; THEODOROU, M K; KATIYAR, D S; PRASAD, S V S; MISHRA, U S; PANDEY, K C; BHASKAR, R B; VERMA, A P S (The Indian Journal of Animal Sciences, 2011)
Based on 2 years evaluation of 6 stay green and 4 go brown sorghum cultivars for nutritional and morphological attributes, 2 promising cultivars each of stay green (M35-1 and CSV-15) and go brown sorghum (HD-20 and J Sel-IO) were gown, harvested 1month after grain collection and then conserved as silage. Silage was fed ad lib. to 16 crossbred sheep divided equally to silage of each cultivar. Metabolism trial was conducted to assess intake, nutrients utilization and N balance, and rumen liquor samples were collected at 0 h to determine the rumen fermentation pattern. The intake of stay green sorghum was higher than go brown. Similarly w0.75 intake of DE, TDN and DCP was higher in sheep fed stay green sorghum silage. Sheep fed stay green sorghum silage had 4-5 units more nutrients digestibility. OM and hemicellulose digestibility was higher in animals fed stay green. N absorption and retention was higher in sheep stay green than go brown sorghum silage. DCP, TDN and DE contents of stay green sorghum were higher than go brown sorghum silage. Mean NH3-N contents were higher in rumen liquor of sheep fed stay green than go brown sorghum silage. Results indicated that silage from stay green sorghunl cultivars is more palatable and nutritious than go brown cultivars. Â